Analysis of the Use of Digital Payment and Financial Report Applications in SMSE - Oktaviani, Nita Fauziah; Yusnita, Rita Tri; Yuniar, Evilia Sri; Listanti, Yeja Firginia; Tujjahra, Dita Raudya; Pamungkas, Muhamad Dito (Journal of International Conference Proceedings, 2023)
Digitalization is increasingly entering the MSME environment, which, if used properly, digitalization will help MSMEs in optimizing their income. One of the dimensions entered by digital is in terms of MSME finance, that is financial reporting applications. This helps several MSMEs in preparing financial reports even though these MSMEs do not have the ability to prepare their own financial reports. Financial reports have various benefits, one of which is to see the financial condition of MSMEs. This research is to find out the use of applications that generate financial reports on MSMEs. This study uses a qualitative method. The results of this research show that MSMEs use various kinds of financial reporting applications for various reasons and have various obstacles in their use, apart from that there are various government policies to support the use of financial reporting applications within the MSMEs sector in Indonesia.